Environmental Performance, Institutional Ownership, And Debt Cost Determinants of Financial Distress - Ifatunisa, Mutia; Purwidianti, Wida; Tubastuvi, Naelati; Fakhruddin, Iwan; Roslan, Nur Hafiza (UNIVED Press, 2026)
This study aims to examine and analyze the effect of environmental performance, institutional ownership, and debt costs on financial distress in companies in the energy, raw materials, and industrial sectors listed on the Indonesia Stock Exchange. This study uses a quantitative approach with secondary data obtained from annual reports. The population of this study is companies in the energy, raw materials, and industrial sectors listed on the IDX from 2020 to 2024. With purposive sampling, there are 155 samples based on PROPER certificate ownership and institutional ownership structure. The analysis was conducted using logistic regression with SPSS 26. The control variables used were Total Asset Turnover (TATO), Firm Age, and Firm Size. The results show that debt costs, TATO, firm age, and firm size have a significant effect on financial distress. Meanwhile, environmental performance and institutional ownership do not have a significant effect on financial distress. This study emphasizes the importance of financing structure management, particularly debt costs, in maintaining corporate financial stability. Debt costs play a decisive role in increasing the risk of financial distress if not managed properly. This study reinforces the relevance of trade-off theory in the context of corporate financing in the energy, raw materials, and industrial sectors.